Research of intensive technology of winter wheat plants and various agricultural approaches in Luhansk region - Маслійов, С. В.; Беседа, О. О.; Дрель, В. Ф.; Арсієнко, В. О. (Scientific Progress & Innovations, 2018)
Nowadays it is difficult to imagine the technology of cultivating grain crops without the use of grow regulators. And this is understandable. After all, speaking about the cost-effective production of grain, we necessarily associate this with an increase in the level of yield, which is impossible without the growth of individual productivity of plants. The use of these drugs in conjunction with the increase in the culture of agriculture and the increase in the use of fertilizers contributed to a significant increase in winter wheat yields not only in experiments, but also in production massifs. However, analysis of the level of yields that was obtained in Luhansk region in next years has shown that its size is not always guaranteed. Especially sharp drop in yields in some years seemed incomprehensible and unacceptable after introducing into the production of techniques based on the use of growth regulators. Analysis of the causes of a sharp drop in winter wheat yields in some years has shown that it is due primarily to the manifestation of epiphytotic diseases – fungal diseases and damage to plant pests. Especially sharp decrease of crops occurs in years when two or almost three of the listed factors appear simultaneously. Scientists came to the conclusion that after introduction of the application of growth retardants into production of high-yielding varieties, it is necessary to carry out the fight against diseases and pests on winter wheat crops. After all, only crops protected from these factors have the opportunity to obtain high yield crops.